Static strength of hot-stamped spot welded joints: study on spot welding tailored blank technology*. Issue 9 (2nd September 2017) - Fujimoto, Hiroki; Yasuyama, Masanori; Ueda, Hideki; Ueji, Rintaro; Fujii, Hidetoshi
Abstract: Hot stamping spot welding tailored blank technology is a process to produce spot welded automotive body parts by the following process: spot welding steel sheets in lap configuration → hot stamping (heating to about 900°C) → quenching and forming in water-cooled die → shot blasting to remove scale. This process has the advantage of producing high strength lap welded automotive body parts without increasing the number of forming dies. In this study, the mechanical properties of the hot stamped spot weld (spot welding → hot stamping) and conventional spot weld (hot stamping → spot welding) of the 1500 MPa class uncoated boron steel sheets were compared. The obtained results are as follows. The tensile shear strength (TSS) of the hot-stamped spot weld and conventional spot weld were comparable and the fracture modes were the same. On the other hand, the cross tension strength (CTS) of hot-stamped spot weld was significantly higher than that of the conventional spot weld. The fracture position of the hot-stamped spot weld was outside the nugget and conventional spot weld was inside the nugget. The high CTS of the hot-stamped spot welds might be caused by the improvement of the fracture toughness of the nugget, which was caused by reduction of the solidification segregation of the phosphorus. It is assumed that the heating process after spot welding leads to the reduction of the solidification segregation. For the tension test because there was no HAZ softening in the hot-stamped spot weld, no fracture was observed in HAZ and a higher elongation was obtained.